Application of Bayesian networks to data mining - Rod, Martin (2018)
This thesis was written to data mine a data set in field of higher education, more specifically examinations of students in bachelor's study programme in one of the Czech public university. The main goal of the thesis was to use proposed Bayesian network as a data mining tool for asserting the differences between full-time and part-time study form. Four Bayesian networks were created and used for knowledge extraction. The found differences and disproportions concerning the successful completion of this particular bachelor's study programme between those study forms were determined and discussed. A definition of key success factors concerning the courses was proposed.